2021
DOI: 10.1021/acsami.0c19010
|View full text |Cite
|
Sign up to set email alerts
|

GC-like Graphene-Coated Quartz Crystal Microbalance Sensor with Microcolumns

Abstract: Many research groups have been interested in the quartz crystal microbalance (QCM)-based gas sensors due to their superb sensitivity originated from direct mass sensing at the ng level. Despite such high sensitivities observed from QCM sensors, their ability to identify gas compounds still needs to be enhanced. Herein, we report a highly facile method that utilizes microcolumns integrated on a QCM gas-responsive system with enhanced chemical selectivity for sensing and ability to identify volatile organic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…They are effective analytical devices [49][50][51]. Compared to traditional methods, they provide label-free and real-time detection, easy use with modern technologies, portable size, high sensitivity, low cost, and basic data analysis [52][53][54].…”
Section: Biosensor Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are effective analytical devices [49][50][51]. Compared to traditional methods, they provide label-free and real-time detection, easy use with modern technologies, portable size, high sensitivity, low cost, and basic data analysis [52][53][54].…”
Section: Biosensor Devicesmentioning
confidence: 99%
“…They are effective analytical devices[49][50][51]. Compared to traditional methods, they provide label-free and real-time detection, easy use with modern technologies, portable size, high sensitivity, low cost, and basic data analysis[52][53][54].It is very important to use accurate and timely detection methods to prevent the progression of a disease and stop the chain of transmission with early diagnosis. Traditional assays are often time-consuming and expensive.…”
mentioning
confidence: 99%
“…Various sensing materials were modified on the surface of QCM electrodes, the dimension, size, and morphology of which determine the adsorption between the sensors and gas molecules . For example, Son et al reported a graphene oxide coated QCM gas sensor with micrometer-scale column-installed for sensing and identifying different gases . Because of the difference in diffusional transfer of gas molecules through the microcolumns, the QCM sensor could identify ethanol, acetone, and hexane.…”
Section: Introductionmentioning
confidence: 99%
“…Here, GQDs find a significant research interest in various optoelectronic applications due to their tunable electro-optical properties and nontoxicity making it an alternative candidate for replacing inorganic QDs. 28,29 The unique optical properties of GQDs make them a favorable material for high gain photodetection materials in a broad wavelength range particularly in the UV range. 30 The UV−visible photodetector has been designed using GQD incorporated ZnO nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently because of the high market cost of inorganic QDs and due to their high toxicity, industrial use of these materials has been restricted. Here, GQDs find a significant research interest in various optoelectronic applications due to their tunable electro-optical properties and nontoxicity making it an alternative candidate for replacing inorganic QDs. , The unique optical properties of GQDs make them a favorable material for high gain photodetection materials in a broad wavelength range particularly in the UV range . The UV–visible photodetector has been designed using GQD incorporated ZnO nanorods. , Studies reported that 80% EQE was obtained within a broad wavelength range in a photodetector based on a graphene quantum dot layer sandwiched between graphene sheets .…”
Section: Introductionmentioning
confidence: 99%